APPLYING BBC LEARNING ENGLISH APPLICATION IN STUDENTS' VOCABULARY MASTERY - Haris Hamdani; Ferawaty Puspitorini (Lexeme : Journal of Linguistics and Applied Linguistics, 2021)
Technology has a crucial role in helping students improve their English skills. One of the devices that help them improve their English skills particularly vocabulary is Smartphone with some applications. One of the applications is BBC Learning English. The aim of this study is to explore the use of BBC Learning English application in students’ vocabulary mastery. This is a qualitative study with case study particularly the phenomenological study. The participants of this study were 26 students of Bhayangkara Jakarta Raya University majoring Accounting in the 4th Semester. The data were collected through questionnaire. The results of the study were that students got 10 new vocabularies for each meeting. 23 students could memorize English vocabularies easily. 21 Students had their spirit increased. 17 students agreed about the number of benefits that they got.16 students agreed that the contents in the application varied.21 studentsliked BBC Learning English application.8 students disagreed and 8 students strongly disagreed about no advantages of the application. 12 students agreed, 7 students disagreed about memorizing vocabularies without using the application.10 students disagreed about being nervous using the application.22 students liked the topics in the application. 21 students agreed that videos in the application helped students memorize vocabularies. 21 studentshad mobile phone-based Android.21 students agreed that the application was very flexible to use.20 students agreed that the application was friendly to use.22 students got fun experience using the application. 21 students were proud of using the application. 21 students agreed that the contents are interesting. 21 students would recommend the application. 20 students could use the application easily. 13 students agreed that mastering vocabularies is important. 17 students had the target to master English vocabularies.